Editorial policy of Kedaulatan Rakyat, Tribun Jogja, and Harian Jogja in reporting regional management by Kasultanan Ngayogyakarta Hadiningrat - Gilang Jiwana Adikara (Informasi, 2022)
The Province of the Special Region of Yogyakarta is an anomaly in a democratic country. The position of regional head in this province is held by the Ngayogyakarta Hadiningrat Sultanate which adheres to a monarchical system so that regional management experiences various obstacles, such as internal palace conflicts or allegations of maladministration. As mass media whose freedom is regulated by law, the three mass media in DIY also have to deal with a unique local government system. This study discusses the editorial policies of three local media in Yogyakarta: Kedaulatan Rakyat, Tribun Jogja, and Harian Jogja regarding the DIY government under the Ngayogyakarta Hadiningrat Sultanate and maps out the factors that influence the editorial policy. Indepth interview were conducted to each of the media representatives to obtain data that then analyzed. This study concludes that each media is more careful in criticizing and controlling the government. Various factors also influence this policy, both at the individual level, media routines, organizations, social institutions, and social systemsThis research concludes that the editorial policy is more careful in the function of control and criticism as well as the existence of various factors both at the individual level, media routines, organizations, social institutions, and social systems that underlie these decisions.